STUDI PERBANDINGAN TENTANG TINDAK PIDANA PORNOGRAFI TERHADAP ANAK MELALUI INTERNET MENURUT HUKUM PIDANA INDONESIA DAN HUKUM PIDANA AUSTRALIA - Handayani, Gusma Putri; Yunaldi, Wendra; Zulfiko, Riki (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Child pornography is a form of sexual exploitation, so Protection of children should receive great attention. There are two dangerous things in child pornography; First, involving children in pornography is equivalent to exploiting children for the worst forms of work. Second, allowing children to access pornography will greatly impact the child's growth and development process. The purpose of this study is to determine the position of children as victims in pornography crimes, to find out legal assistance for children as victims of pornography crimes, and to find out criminal law policies towards children as victims of pornography crimes. Based on the background of the problem, it is formulated that the problem is 1) How is the regulation of child pornography law in Indonesian Law 2) How is the regulation of child pornography law in Australian Law 3) How does the regulation of pornography against children through the internet in Indonesian law and Australian Law compare.